Cross-ethnic Relations Through Association Participation Among Youth in Pasir Gudang, Johor - Kamri, Khairol Anuar; Abd Hamid, Aizatul Hani; Abdullah, Muhaymin Hakim; Mohammed Zabidi, Ahmad Fakhrurrazi; Chang Peng Kee (Journal of Techno-Social, 2022)
The youth are in a phase of identity fragility which causes them to often engage in behavior that touches on issues of ethnic sensitivity. Therefore, cross-ethnic social relations among the youth need to be constantly monitored because they are the future heirs of the country. Cross-ethnic social relations in this study are examined through the pattern of cross-ethnic associations among youth. This study involved 362 youth (60% Malay, 25% Chinese and 15% Indian). Data were obtained from the distribution of questionnaires which were analyzed using SPSS version 23 and SMART-PLS 3.0 software. The findings of the pattern show that Malay youth have more cross-ethnic social relationships through associational activities compared to Chinese and Indian youth. Contributions and suggestions for further research are included in the conclusion section of the study. Golongan belia berada dalam fasa kerapuhan identiti yang menyebabkan mereka sering terlibat dalam tingkah laku yang menyentuh isu sensitiviti etnik. Maka, hubungan sosial rentas etnik dalam kalangan belia perlu sentiasa dipantau kerana mereka adalah pewaris masa hadapan negara. Hubungan sosial rentas etnik dalam kajian ini diteliti melalui pola berpersatuan rentas etnik dalam kalangan belia. Kajian ini melibatkan 362 belia (Melayu 60%, Cina 25% dan India 15%). Data diperoleh daripada pengedaran soal selidik yang dianalisis menggunakan perisian SPSS versi 23 dan SMART-PLS 3.0. Dapatan pola menunjukkan belia Melayu lebih terbina hubungan sosial rentas etnik melalui aktiviti berpersatuan berbanding belia Cina dan India. Sumbang dan cadangan kajian lanjut disertakan dalam bahagian kesimpulan kajian.